Tiger Force a true story of men and war - Sallah, Michael; Weiss, Mitch (Little, Brown, 2006)
The true story of the seven-month rampage of an elite army unit in Vietnam, an experiment gone terribly wrong, is told from the viewpoints of the soldiers who tried to resist the descent into hell, and those who did not, and includes accounts from Vietnamese who witnessed the Tiger Force's rampages. It is also the story of how these atrocities, covered up by the Army for decades, came to light at last through the heroic persistence of a few individuals who could not forget. Journalists Sallah and Weiss won the 2004 Pulitzer Prize for investigative reporting for their series in the Toledo Blade on the last great secret of the Vietnam War.--Adapted from publisher description.
The true story of the seven-month rampage of an elite army unit in Vietnam, an experiment gone terribly wrong, is told from the viewpoints of the soldiers who tried to resist the descent into hell, and those who did not, and includes accounts from Vietnamese who witnessed the Tiger Force's rampages. It is also the story of how these atrocities, covered up by the Army for decades, came to light at last through the heroic persistence of a few individuals who could not forget. Journalists Sallah and Weiss won the 2004 Pulitzer Prize for investigative reporting for their series in the Toledo Blade on the last great secret of the Vietnam War.--Adapted from publisher description.
Includes bibliographical references and index
Keywords: United States -- Army -- Infantry Regiment, 327th -- Battalion, 1st -- Tiger Force Platoon -- History; USA -- Infantry Regiment -- 327 -- Battalion -- 1; Infanterie; Oorlogsmisdaden; Regimenten; Vietnam-oorlog; Geschichte; Vietnamkrieg; Vietnam War, 1961-1975 -- Regimental histories -- United States; Vietnam War, 1961-1975 -- Atrocities; USA; Erlebnisbericht